2016
DOI: 10.1111/jsr.12471
|View full text |Cite
|
Sign up to set email alerts
|

Objective snoring time and carotid intima‐media thickness in non‐apneic female snorers

Abstract: Controversy persists about whether snoring can affect atherosclerotic changes in adjacent vessels, independent of obstructive sleep apnea and other cardiovascular risk factors. This study examined the independent association between snoring and carotid artery intima-media thickness (IMT) in nonapneic snorers and nonsnorers. We studied 180 nonapneic snorers and nonsnorers undergoing in a full-night home-based sleep study. Snoring sound was objectively measured by a microphone. Based on snoring time across the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The mechanisms underlying the relationship between simple snoring and MetS have not been clarified. Through direct mechanical injury to the endothelium and local initiation of proinflammatory response, snoring vibration transmission may accelerate the development of carotid atherosclerotic plaque and contribute to MetS [37–40]. The physiological disturbances caused by snoring increase the number of microarousals during sleep [22], which could disrupt the restorative value of sleep, increase the activity of the sympathetic nervous system, and have a harmful impact on the hypothalamic-pituitary-adrenal axis with consequent elevations in serum cortisol, ultimately contributing to metabolic dysfunction [13, 4145].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the relationship between simple snoring and MetS have not been clarified. Through direct mechanical injury to the endothelium and local initiation of proinflammatory response, snoring vibration transmission may accelerate the development of carotid atherosclerotic plaque and contribute to MetS [37–40]. The physiological disturbances caused by snoring increase the number of microarousals during sleep [22], which could disrupt the restorative value of sleep, increase the activity of the sympathetic nervous system, and have a harmful impact on the hypothalamic-pituitary-adrenal axis with consequent elevations in serum cortisol, ultimately contributing to metabolic dysfunction [13, 4145].…”
Section: Discussionmentioning
confidence: 99%
“…A study of 180 non-apnoeic snorers and non-snorers, based on full-night home-based polysomnography, showed that mean CIMT increased with increased snoring time throughout the night in women but not in men [ 51 ]. Therefore, because studies have shown a direct correlation between CIH and biomarkers, snoring could be an additional minor contributor in women.…”
Section: The Impact Of Obstructive Sleep Apnoea On Cardiovascular Risk Factorsmentioning
confidence: 99%
“…In a large study by Kim et al, 180 participants undergoing home‐based full‐night sleep studies had their snoring noises recorded via microphones. Based on snoring time as a percentage of total sleep time, patients were categorized as nonsnorers (0%), mild snorers (1% to 25%), and moderate to heavy snorers (more than 25% snoring time).…”
Section: Literature Reviewmentioning
confidence: 99%